Parental grief following infant death in the NICU: a longitudinal mixed-methods exploration of parental experiences and influencing factors - Emily Kieran; Esther Alonso-Prieto; Rachelle Chung; Kelly Allison; Marie Nightbird; Susan Albersheim (BMJ Open)
Objectives To characterise neonatal intensive care unit (NICU) parents’ grieving process across time and to identify their perspectives on the healthcare providers’ actions that acted as facilitators or barriers to the grieving process in the short (3–9 months) and longer term (18–24 months).Design Longitudinal mixed-methods study combining standardised grief and care satisfaction scales with qualitative data collected through semistructured interviews. The qualitative component was guided by an interpretive description approach, which is well-suited for generating clinically relevant insights into complex human experiences such as parental grief. Triangulating quantitative and qualitative data enhanced insight into how parental grief and perceptions of care evolved between 3–9 months and 18–24 months post loss.Setting Tertiary-level NICU hospital in British Columbia, Canada.Participants 13 parents participated in the study, including 10 mothers and three fathers. Among them were two couples who participated as individuals. Their median age was 35 years (IQR: 32–38).Primary and secondary outcome measures Quantitative data obtained through the application of the Perinatal Grief Scale (PGS) and care satisfaction scale and qualitative data collected through semistructured interviews. Data were collected at two points (3–9 months and 18–24 months post loss) to track parents’ grief over time.Results The PGS scores indicated active grieving without complicated grief, while the Care Satisfaction Scale reflected high overall satisfaction with care. Thematic analysis identified two primary grieving stages: the initial traumatic event during NICU hospitalisation and the complex adjustment to life post loss. Key factors influencing parents’ coping mechanisms included respecting the infant’s dignity, enhancing communication and decision-making, preserving the bond between parents and the NICU team, nurturing enduring connections with the infant and aiding in finding meaning from the experience.Conclusion The study outlined the stages parents experience during and after infant loss, offering practical steps for NICU professionals to aid families in their healing process.